Ocean ventilation and anthropogenic carbon based on evaluated transient tracer applications - Stöven, Tim (2015)
This thesis includes three manuscripts. The first describes the ventilation of the Mediterranean Sea in 2011 based on multiple transient tracer measurements. The second evaluates the application of different transient tracers and the IG-TTD model by using several data sets from the South Atlantic and Southern Ocean. The third manuscript intorduces a new theory about saturation states of transient tracers and provides a flux estimate of anthropogenic carbon through Fram Strait in 2012. Diese Dissertation besteht aus drei Manuskripten. Das erste Manuskript beschreibt die Ventilation des Mittelmeeres in 2011 basierend auf mehreren Spurengasmessungen. Das zweite Manuskript evaluiert die Anwendung von Spurengasen und dem IG-TTD Modell anahand diverser Datensätze aus dem Südatlantik und dem Südlichem Ozean, Das dritte Manuskript führt eine neue Theorie über Sättigungszustände der Spurengase ein und beeinhaltet eine Flussabschätzung von anthropogenem Kohlenstoff durch die Fram Straße in 2012.